The Influence of Ice-Resistant Coatings Characteristics to the Energy Efficiency of Ice-Going Ships - Veselov V.A. (EDP Sciences, 2021)
The main purpose of ice-resistant coatings designed for icebreakers and ice navigation ships is the ability to protect of the ship’s hull in the most severe operating conditions. The special coatings certified by the Classification Societies for ice abrasion can provide this protection. These coatings allow to reduce the required thickness of the ship’s hull and reduce the construction weight of the ships. On the other hand, these coatings must have a low friction coefficient, which reduce the frictional resistance of the hull on ice and fuel consumption, increase the service life of the ship and power plant, reduce CO2 emissions into the atmosphere and affect to the operational and economic efficiency of the ship. In this paper, we present the results of experimental tests of friction coefficient on ice for various types of ice-resistant coatings and analysis the influence of ice-resistant coatings characteristics to the energy efficiency of ice-going ships.